2019
DOI: 10.1016/j.joule.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Dot-Derived Catalysts for CO2 Reduction Reaction

Abstract: A high density of homogeneously dispersed atomic defects has long been believed to be a promising strategy for improving catalytic activity. Taking the defective nature of quantum dots, Liu et al. synthesize vacancy-rich metal nanocrystals through in situ electrochemical reduction of quantum dots. This maximizes the density and stability of vacancies in metallic nanocrystals and achieves record current densities with high faradic efficiencies in the electrosynthesis of formate, carbon monoxide, and ethylene at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 56 publications
2
76
0
Order By: Relevance
“…Electrochemical reduction of CO 2 to valuable chemical feedstocks or fuels using renewable electricity contributes to closing the artificial carbon cycle. [ 1 ] The sophisticated multi‐electron transfer process leads to a multitude of possible CO 2 reduction products ranging from C 1 (CH 4 , [ 2 ] CO, [ 3 ] HCOOH [ 4 ] ) to C 2+ (C 2 H 5 OH, [ 5 ] CH 3 COOH, [ 6 ] C 2 H 4 , [ 7a,b ] C 2 H 6 , [ 7c ] and CH 3 CH 2 CH 2 OH [ 5 ] ) productions, especially for copper‐based catalysts. [ 7d ] Even though the C 2+ products possess higher industrial values, [ 8 ] CO 2 electroreduction to C 2+ products in industrial level remains a substantial challenge due to its low selectivity and sluggish reaction pathway, eventually resulting in high production cost.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical reduction of CO 2 to valuable chemical feedstocks or fuels using renewable electricity contributes to closing the artificial carbon cycle. [ 1 ] The sophisticated multi‐electron transfer process leads to a multitude of possible CO 2 reduction products ranging from C 1 (CH 4 , [ 2 ] CO, [ 3 ] HCOOH [ 4 ] ) to C 2+ (C 2 H 5 OH, [ 5 ] CH 3 COOH, [ 6 ] C 2 H 4 , [ 7a,b ] C 2 H 6 , [ 7c ] and CH 3 CH 2 CH 2 OH [ 5 ] ) productions, especially for copper‐based catalysts. [ 7d ] Even though the C 2+ products possess higher industrial values, [ 8 ] CO 2 electroreduction to C 2+ products in industrial level remains a substantial challenge due to its low selectivity and sluggish reaction pathway, eventually resulting in high production cost.…”
Section: Figurementioning
confidence: 99%
“…Conversely, several recent studies have shown the production of C 1 products including CO and HCOOH is more economically viable and has the great prospect of industrialization. [ 3a,b,4b,9 ] Moreover, compared to the gas production of CO, the stable liquid HCOOH product is more beneficial to the separation and collection in the preparation and storage. [ 9d,e ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A variety of products ranging from hydrocarbons to oxygenates [9][10][11][12][13][14][15][16][17] and from C 1 to C 3 can be produced from CO 2 RR using different catalytic materials [18][19][20][21][22][23][24] . As the price of renewable electricity continues to decrease, the cost of some CO 2 RR products, particularly those single carbon molecules such as carbon monoxide (CO) and formate, becomes competitive to traditional chemical engineering processes due to their industrially relevant selectivity (>90%) and activity (>100 mA cm −2 ) [25][26][27][28][29][30][31][32][33][34][35][36] . Compared with gas-phase CO 2 RR products, liquid products such as formate show significant advantages due to their high energy densities and ease of storage and distribution 37,38 .…”
mentioning
confidence: 99%
“…Novel and highly stable electrocatalysts are currently being developed and tested; these include quantum dot [136], carbon nanostructure-based [137] electrocatalysts, among others. More investigations are needed to quantify the intensification level of these potential materials.…”
Section: Electrochemical Conversionmentioning
confidence: 99%